2017
DOI: 10.3892/etm.2017.4823
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in combination with rosiglitazone contribute to the increased serum adiponectin levels in people with type 2 diabetes mellitus

Abstract: To evaluate how metformin plus rosiglitazone affect serum adiponectin levels in people suffering from type 2 diabetes mellitus (T2DM), 240 patients having T2DM were selected in this cohort study. Included subjects were randomly and equally separated into three subsets: i) Group A (rosiglitazone group); ii) group B (metformin group); and iii) group C (rosiglitazone + metformin group). Furthermore, meta-analysis of previous studies was performed by searching the general search engines and bibliographic databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Adiponectin, secreted by adipocytes, is an insulin-sensitizing hormone (15), improving insulin resistance in mice (37). And in studies on humans, adiponectin has the potential to be a biomarker for predicting metabolic diseases such as diabetes mellitus (38). In clinical trials, adiponectin was demonstrated to exhibit anti-diabetic (39), anti-atherosclerotic (40) and anti-cancer potential (41).…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin, secreted by adipocytes, is an insulin-sensitizing hormone (15), improving insulin resistance in mice (37). And in studies on humans, adiponectin has the potential to be a biomarker for predicting metabolic diseases such as diabetes mellitus (38). In clinical trials, adiponectin was demonstrated to exhibit anti-diabetic (39), anti-atherosclerotic (40) and anti-cancer potential (41).…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were as follows: pancreatic exocrine diseases, pancreatic lesions, and other pancreatic diseases; heavy drinkers, defined as drinking >280 g alcohol/wk for men and >140 g/wk for women; [ 10 ] patients using lipid-lowering drugs, such as statins and fibrates, [ 12 – 14 ] and patients using antidiabetic drugs that affect serum adipocytokine or endogenous GLP-1 levels, such as metformin, thiazolidinediones, GLP-1 receptor agonists and dipeptidyl peptidase 4 (DPP4) inhibitors; patients with various conditions such as infection, trauma, serious bleeding, severe brain, and kidney complications; and patients with a variety of acute complications of diabetes such as diabetic ketosis, hypertonic diabetic coma, other diabetic comorbidities (such as cancer, disease of immune system, or hematologic system). (5) Pregnant or lactating, menstrual women.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, thiazolidinediones (TZDs) such as rosiglitazone and pioglitazone, PPARγ agonists used for decades to treat type 2 diabetes due to its insulin sensitization activity (Saltiel and Olefsky, 1996; Malinowski and Bolesta, 2000; Hong et al, 2018) were recently repurposed to treat AD. The insulin-sensitizing effect of TZDs is in part mediated by induction of peripheral adiponectin and AdipoRs expression (Yu et al, 2002; Tsuchida et al, 2005; Nie and Li, 2017). Therefore, it is possible that adiponectin mediate part of the observed beneficial effects of donepezil and TZDs.…”
Section: Adiponectinmentioning
confidence: 99%